Influence of oral motor tasks on postural muscle activity during dynamic reactive balance. - Hellmann, Daniel; Fadillioglu, Cagla; Kanus, Lisa; Möhler, Felix; Schindler, Hans J.; Schmitter, Marc; Stein, Thorsten; Ringhof, Steffen (Journal of Oral Rehabilitation, 2024)
Background: Jaw clenching improves dynamic reactive balance on an oscillating platform during forward acceleration and is associated with decreased mean sway speed of different body regions. Objective: It is suggested that jaw clenching as a concurrent muscle activity facilitates human motor excitability, increasing the neural drive to distal muscles. The underlying mechanism behind this phenomenon was studied based on leg and trunk muscle activity (iEMG) and co‐contraction ratio (CCR). Methods: Forty‐eight physically active and healthy adults were assigned to three groups, performing three oral motor tasks (jaw clenching, tongue pressing against the palate or habitual lower jaw position) during a dynamic one‐legged stance reactive balance task on an oscillating platform. The iEMG and CCR of posture‐relevant muscles and muscle pairs were analysed during platform forward acceleration. Results: Tongue pressing caused an adjustment of co‐contraction patterns of distal muscle groups based on changes in biomechanical coupling between the head and trunk during static balancing at the beginning of the experiment. Neither iEMG nor CCR measurement helped detect a general neuromuscular effect of jaw clenching on the dynamic reactive balance. Conclusion: The findings might indicate the existence of robust fixed patterns of rapid postural responses during the important initial phases of balance recovery.